Sphere-based Information Visualization: Challenges and Benefits - Brath, Richard; MacMurchy, Peter (IV'12: Proceedings of the International Conference on Information Visualisation, 2012)
Use of a sphere as a basis for organizing an information visualization should balance issues such as occlusion against potential useful benefits such as natural navigational affordances and perceptual connotations of an application.